An Asymptomatical Adult Diastematomyelia Together with Pedicular Bone Defect: CT and MRI Findings - Kavaklı, Ahmet; Yıldırım, Hanefi; Ögetürk, Murat; Kuş, İlter; Köse, Evren; Sarsılmaz, Mustafa (Fırat University, 2007)
Diastematomyelia (DM); is a condition characterized with division of the spinal cord into two hemicords by a cartilaginous, osseous or fibrous septum. In about 50% of the cases, the spinal cord is involved, while in the remaining half the hemi-cords are contained in subarachnoid space or across the spinal canal. DM, can involve all segments of the spinal cord. A 27 years old female patient admitted with complaint of backache and urinary for about a year. Computerized tomography (CT) scan and magnetic resonance imaging (MRI) revealed that the spinal cord dividing into two hemicords by an osseous septum from forward to backward at the level of L2-3. There was also evident pedicular bone defect on the right sight of the vertebrae at the level of L5. We present this case due to rarity of association of DM and pedicular bone defect and its silent course till this adult age. ©2007, Fırat University, Medical Faculty

Diastematomyelia (DM); Medulla Spinalis'in (MS) kemik, kıkırdak veya fibroz bir septum ile ikiye ayrılmasıdır. Olguların %50'sinde MS olaya katılır, diğer yarısında yalnız subaraknoid boşluk veya canalis vertebralis ikiye ayrılır. DM, MS'in tüm segmentlerinde görülebilir. Yaklaşık bir yıldır bel ağrısı ve üriner şikayetleri olan 27 yaşındaki bir kadın hastanın yapılan Bilgisayarlı Tomografi (BT) ve Manyetik Rezonans Görüntüleme (MRG) tetkikleri sonucunda, L2-3 seviyesinde MS'in önden arkaya doğru kemik bir septumla ikiye ayrıldığı diastematomyelia olgusu tespit edildi. Bununla birlikte aynı olguda L5 düzeyinde corpus vertebra'nın sağ pedikülünde kemik defekti mevcuttu. Pediküler kemik defektinin DM ile birlikte olması ve erişkin yaşa kadar bulgu vermemesi nedeniyle önemli olduğunu düşünmekteyiz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Pediküler Kemik Defektinin Eşlik Ettiği Asemptomatik Adult Diastematomyelia: BT ve MRG Bulguları